CIGALA: Challenging the Solar Maximum in Brazil with PolaRxS - Bougard, B.; Sleewaegen, J-M; Spogli, L.; Veettil, Sreeja Vadakke; Galera Monico, J. F. [UNESP]; ION (Inst Navigation, 2011)
The upcoming solar maximum, which is expected to reach its peak around May 2013, occurs at a time when our reliance on high-precision GNSS has reached unprecedented proportions. The perturbations of the ionosphere caused by increased solar activity pose a major threat to these applications. This is particularly true in equatorial regions where high exposure to solar-induced disturbances is coupled with explosive growth of precise GNSS applications. Along with the various types of solar-induced ionospheric disturbances, strong scintillations are amongst the most challenging, causing phase measurement errors up to full losses of lock for several satellites. Brazil, which heavily relies on high-precision GNSS, is one of the most affected regions due notably to the proximity to the southern crest of the ionospheric equatorial anomaly and to the South Atlantic Magnetic Anomaly. In the framework of the CIGALA project, we developed the PolaRxS(TM), a GNSS receiver dedicated to the monitoring of ionospheric scintillation indices not only in the GPS L1 band but for all operational and upcoming constellations and frequency bands. A network of these receivers was deployed across the whole Brazilian territory in order to first investigate and secondly to mitigate the impact of scintillation on the different signals, ensuring high precision GNSS availability and integrity in the area. This paper reports on the validation of the PolaRxS(TM) receiver as an ionospheric scintillation monitor and the first results of the analysis of the data collected with the CIGALA network.